2012
DOI: 10.1001/archpediatrics.2011.197
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Fortified vs Low-Iron Infant Formula

Abstract: Objective: To assess long-term developmental outcome in children who received iron-fortified or lowiron formula.Design: Follow-up at 10 years of a randomized controlled trial (1991)(1992)(1993)(1994) of 2 levels of formula iron. Examiners were masked to group assignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 37 publications
2
75
1
3
Order By: Relevance
“…In this study, there was an increased likelihood of diarrhoea in a sub-group of infants with adequate iron status. In a follow-up of the study by Walter et al (1998) at 10 years of age (Lozoff et al, 2012), scores on tests for spatial memory and visual motor integration, but not on tests for IQ, visual perception, motor coordination and arithmetic achievement, were statistically significantly lower in the group who had received high-iron formula (1.95 mg/100 kcal). Effects were generally small.…”
Section: Health Consequencesmentioning
confidence: 87%
“…In this study, there was an increased likelihood of diarrhoea in a sub-group of infants with adequate iron status. In a follow-up of the study by Walter et al (1998) at 10 years of age (Lozoff et al, 2012), scores on tests for spatial memory and visual motor integration, but not on tests for IQ, visual perception, motor coordination and arithmetic achievement, were statistically significantly lower in the group who had received high-iron formula (1.95 mg/100 kcal). Effects were generally small.…”
Section: Health Consequencesmentioning
confidence: 87%
“…Although the prevalence of IDA is relatively low in large parts of Europe, iron deficiency in infants and young children is still a public health priority as children with depleted iron stores but without anaemia at 1 year of age might have lower fine motor and mental development scores in later childhood than children with sufficient iron stores [10,79,80,81,82,83]. On the other hand, it has been suggested that supplemental iron in infants with high Hb levels may adversely affect neurodevelopmental outcome [84]. Defining optimal amounts of iron in iron-fortified milk and foods is therefore of upper most importance.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies on an adverse effect on linear growth of iron drops given to iron-replete infants (10) and observations by others caused Lozoff et al (32) to re-examine data from a previous large intervention study that they had conducted in Chilean infants who were given infant formula with 2 amounts of iron fortification (33).…”
Section: Effects Of Iron Excess On Cognitive Devel-opment Of Iron-repmentioning
confidence: 93%